Sensory Analysis of Puff Snacks: Impact of Tempeh Powder Addition on Product Quality - nastiti, julia; djiuardi, evelyn; listyorini, niken taufiqurrahmi; nurfitriana, siti; kusumawati, lucia (Liaison Journal of Engineering, 2024)
Tempeh is a fermented food by the fungus Rhizopus Oligosporus and is made from soybean seeds which are rich in protein and dietary fiber. Tempeh has become a food choice that is rich in nutrients and has broad health potential. In this study, tempeh was incorporated into puff snacks using an extrusion machine as a substitute for wheat flour, aiming to determine the optimal formula. Different percentages of tempeh flour (5%, 10%, 15%, 20%, and 25%) were used. Organoleptic testing was conducted to assess the preferred formula. The findings of the organoleptic evaluation of the use of tempeh flour with a substitution rate of up to 10% were well received in terms of sensory attributes. Keywords: Tempeh; organoleptic; puff snacks; extrusion; protein